Multi-device trust transfer: Can trust be transferred among multiple devices? - Okuoka, Kohei; Enami, Kouichi; Kimoto, Mitsuhiko; Imai, Michita (Frontiers in Psychology, 2022)
Recent advances in automation technology have increased the opportunity of collaboration between humans and multiple autonomous systems such as robots and self-driving cars. In research on autonomous system collaboration, the trust users have in autonomous systems is an important topic. Previous research suggests that the trust built by observing a task can be transferred to other tasks. However, such research did not focus on trust in multiple different devices but of one device or several of the same devices. Thus, we do not know how trust changes in an environment involving the operation of multiple different devices such as a construction site. We investigated whether trust can be transferred among multiple different devices, and investigated the effect of two factors: the similarity among multiple devices and agency attributed to each device, on trust transfer among multiple devices. We found that the trust a user has in a device can be transferred to other devices and that attributing different agency to each device can clarify the distinction among devices, preventing trust from transferring.